Quality by Design Driven Improved Process of Abiraterone Acetate - Annapurna, Sasikala Cheemalapati Venkata; Rao, Srinivas Talasila; Bathini, Pavan Kumar; Gaddameedhi, Prashanth Reddy; Komati, Shravan Kumar; Manda, Amarendhar; Nahide, Pradip D.; Reddy, B Ramalinga; Madhra, Mukesh Kumar; Annapragada, Ratnamala; Bandichhor, Rakeshwar (Synthesis, 2025)
Abiraterone is an antiandrogen and selective inhibitor of 17α-hydroxylase/C17,20-lyase (CYP17) and is currently used in the treatment of metastatic castration-resistant prostate cancer and metastatic high-risk castration-sensitive prostate cancer. Here an improved kilogram scale synthesis of Abiraterone is presented, starting from commercially available dehydroepiandrosterone (DHEA) by employing Quality by Design (QbD) principles, statistical design of experiments (DoE), and green metrics parameters to evaluate the environmental impact and efficiency. This article focuses on identifying critical quality attributes (CQAs), exploring the relationship between CQAs and material attributes (MAs), and determining the critical process parameters (CPPs) for synthesizing hydrazone, vinyl iodide intermediates, and the final product, Abiraterone acetate. The presented approach effectively managed critical impurities and achieved impressive yields of 98, 84, and 78% with purity >99% in the hydrazone, vinyl iodide intermediate, and final API, respectively. The improved synthesis was optimized and scaled for multi-kilogram batches, addressing challenges from previous methods and yielding ICH quality material in 65% overall yield.
Keywords: design of experiments; quality by design; green chemistry; abiraterone acetate; dehydroepiandrosterone